Power in uncertain times : strategy in the fog of peace - Goldman, Emily O., 1961- (Stanford University Press, 2011)
This book examines America's evolving strategy on the international security environment, and comprehensively analyzes how different strategies position states to compete in the present and future, manage risk, and prevail despite uncertainty.